The Role of Dietary Supplements in Depression and Anxiety – A Narrative Review - Hoffmann, Knut; Emons, Barbara; Brunnhuber, Stefan; Karaca, Sedya; Juckel, Georg (Pharmacopsychiatry, 2019)
Introduction Dietary supplements are very widely used in the general population and there is a growing market for them, which is against the recommendations of the German Society for Nutrition. There is some evidence that dietary supplements are useful additions in the treatment of psychiatric disorders. This review is an overview of available practical knowledge regarding the use of supplements in psychiatric treatment. In particular, the review focused on the diagnosis of depression and anxiety in terms of supplement treatment.Methods This is a narrative review of the evidence regarding supplements for treating anxiety and depression. We searched PubMed to 2018. Two reviewers screened the citations and abstracted the data. Phytopharmaceutical attends and animal-based data were excluded.Results There are strong indications regarding the impact of supplements on the selected psychiatric disorders, but at this time, there only a few randomized clinical studies available, so evidence for these findings is quite low. However, it must be noted that there are strong hints for a relationship between vitamin D level and depression. Furthermore, various supplements have got potentially an influence on the characteristics of depression.Discussion This review summarizes the current knowledge about supplements when used for some psychiatric conditions, but the data does not provide compelling evidence in any direction. There are only indications that there is an influence of supplements on psychiatric diseases. In support of this, there is further need for high-quality studies in this field. Reviews on other diagnoses, such as schizophrenia and dementia, will be part of further work.
Keywords: supplements; depression; anxiety